(3GJLGgGJ eYdej GdMdbI GdKGdKI ef GdJYdje GdCSGSj aj HjQhJ fMh eOjQ GdeOQSI hYdGbJgG HCOGFge Gdegfjs - (3GdEScfOQGfj, SYGOs ((3HjQhJs (3GdLGeYI GddHfGfjI(B. (3cdjI GdJQHjI(B. (3GdYeGOIs, 2007)
(3JgOa gPg GdOQGSI Edi GdJYQa Ydi hGbY GJLGgGJ GdeYdejf hGdcTa Yf eOi GQJHGW gPg GdGJLGgGJ HCOGA GdeYdejf Gdegfj hHeJZjQGJ YOjOI CNQi hgj(B: (3GdYeQ, hGdLfS hGdeDgd GdYdej, GdNHQI aj eLGd GdJYdje hGdEOGQI GdeOQSjI deOjQ GdeOQSI, HGdEVGaI Edi LfS GdeYde(B. (3JchfJ YjfI GdHMK GdCSGSjI ef (B35 (3eYdeG h(B76 (3eYdeI ddMdbI GdKGdKI ef GdJYdje GdCSGSj h(B13 (3eOjQG heOjQI ehRYjf Ydi GdeOGQS GdQSejI aj eMGaXI HjQhJ(B. (3WdH ef GdeYdejf GdPjf TedJge GdYjfI JYHFI GSJHGfI HZjI GdJYQa Ydi GJLGgGJge fMh eOjQjge, cPdc WdH ef GdeOjQjf JYHFI GSJHGfI dbjGS caGjGJ eYdejge GdegfjI(B. (3abGeJ GdHGMKI HHfGA GSJHjGfGJ gPg GdOQGSI hJCcOJ ef UObgG hKHGJgG(B. (3hJVefJ GdGSJHGfI GdChdi GdNGUI HGJLGgGJ GdeYdejf (B64 (3YHGQI ehRYI Ydi GdeLGdGJ GdKdGKI GdJGdjI(B: (3JUhQGJ GdeYdejf Mhd NUGd GdeOjQ GdaYdjI, heTGYQ GdeYdejf fMh GdeOjQ hJUQaGJ GdeYdejf eY GdeOjQ(B. (3CeG GdGSJHGfI GdeNUUI ddcTa Yf caGjGJ GdeYdejf GdegfjI abO GTJedJ Ydi (B41 (3YHGQI, hJqhRYJ Ydi CQHYI eLGdGJ gj(B: (3caGjGJ GdJOQjS, caGjGJ EOGQI GdUa, caGjGJ GdGJUGd hGdJaGYd GdUaj, hcaGjGJ GdYdGbGJ GdHjfjI(B. (3hbO JhUdJ GdOQGSI Edi GdfJGFL GdJGdjI(B: 1) (3gfGc GQJHGW EjLGHj Hjf GJLGgGJ GdeYdejf fMh eOjQ GdeOQSI hCOGFge Gdegfj(B. 2) (3dG jhLO GQJHGW Hjf GJLGgGJ GdeYdejf fMh eOjQ GdeOQSI hYeQ gPG GdeOjQ(B. 3) (3dG jhLO GQJHGW Hjf GJLGgGJ GdeYdejf fMh eOjQ GdeOQSI hNHQI GdeOjQ aj eLGd GdEOGQI GdeOQSjI(B. 4) (3dG jhLO GQJHGW Hjf GJLGgGJ GdeYdejf fMh eOjQ GdeOQSI hNHQI GdeOjQ aj egfI GdJYdje(B. 5) (3dG jhLO GQJHGW Hjf GJLGgGJ GdeYdejf fMh GdeOjQ heDgd GdeOjQ GdYdej(B. 6) (3dG jhLO GNJdGa Hjf GJLGgGJ GdeYdejf hGJLGgGJ GdeYdeGJ JHYG dLfSge fMh eOjQ eOQSJge(B. 7) (3dG jhLO GNJdGa Hjf GJLGgGJ GdeYdejf fMh GdeOjQjf Ch GdeOjQGJ(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Beirut; Beyrouth; Cycle moyen; Gestion scolaire; Intermediate Education; Les Attitudes et conceptions des enseignants; Teachers attitudes and conceptions School management; (3GdeQMdI GdeJhSWIs; (3HjQhJs; (3ehGba GdeYdejf hJUhQGJge GdGOGQI GdeOQSjIs